The Removal of Terasil Navy Blue Dye from Al-Kut Textile Wastewater Using Membrance Technologies - Asal Gzar, Hatem; khalid shhaieb, Zahraa (International Journal of Engineering and Technology, 2018)
The current work was devoted to study the operating feasibility using membranes which were manufactured locally, two membrance types were tested nanofiltration (NF) and ultrafiltration (UF) membrane to treat the effluent of Al-kut textile industry. Based on the usage rate in Iraq textile industries, terasil navy blue (TNB) is one of the common disperse dyes discharged in effluent wastewater. Therefore this type of dyes was selected to experience in this study. Parameters such as effects of TNB concentration, feed temperature and operating pressure and its effect on permeate flux noticed and the TNB rejection were investigated. The results show that when using NF system at pressure of 10 bar and when the temperature increased from 25ºC to 37ºC, it was found that an increase in permeate flux from 46.97 to 50 LMH.  However, in UF system permeate flux was increased from 41.32 to 45.04 LMH.  While dye removal was decline in NF membrane from 96.00 to 95.14 and for UF from 79.50 to 78.67 when the temperature raised from 25ºC to 37ºC.The pressure state positive effects on dye removal for both membranes, it show that NF membrane is better in treatment than UF membrane.